High-resolution genome-wide in vivo footprinting of diverse transcription factors in human cells - Boyle, Alan P.; Song, Lingyun; Lee, Bum-Kyu; London, Darin; Keefe, Damian; Birney, Ewan; Iyer, Vishwanath R.; Crawford, Gregory E.; Furey, Terrence S.

(untitled) (Genome Research, 2011)
Regulation of gene transcription in diverse cell types is determined largely by varied sets of cis-elements where transcription factors bind. Here we demonstrate that data from a single high-throughput DNase I hypersensitivity assay can delineate hundreds of thousands of base-pair resolution in vivo footprints in human cells that precisely mark individual transcription factor–DNA interactions. These annotations provide a unique resource for the investigation of cis-regulatory elements. We find that footprints for specific transcription factors correlate with ChIP-seq enrichment and can accurately identify functional versus nonfunctional transcription factor motifs. We also find that footprints reveal a unique evolutionary conservation pattern that differentiates functional footprinted bases from surrounding DNA. Finally, detailed analysis of CTCF footprints suggests multiple modes of binding and a novel DNA binding motif upstream of the primary binding site.